Facilitators and barriers to implementation of integrated community case management of childhood illness: a qualitative case study of Kapiri Mposhi District - Johnson Vonje Riri; Adam Silumbwe; Chris Mweemba; Joseph Mumba Zulu (BMC, 2022)
Abstract Background Zambia adopted the Integrated Community Case Management (ICCM) of childhood illness strategy in May 2010, targeting populations in rural communities and hard-to-reach areas. However, evidence suggests that ICCM implementation in local health systems has been suboptimal. This study sought to explore facilitators and barriers to implementation of ICCM in the health system in Kapiri Mposhi District, Zambia. Methods Data were gathered through 19 key informant interviews with district health managers, ICCM supervisors, health facility managers, and district health co-operating partners. The study was conducted in Kapiri Mposhi district, Zambia. Interviews were translated and transcribed verbatim. Data were were analyzed using thematic analysis in NVivo 11(QSR International). Results Facilitators to implementation of ICCM consisted of community involvement and support for the program, active community case detection and timeliness of health services, the program was not considered a significant shift from other community-based health interventions, district leadership and ownership of the program, availability of national and district-level policies supporting ICCM and engagement of district co-operating partners. Program incompatibility with some socio-cultural and religious cotexts, stock-out of prerequisite drugs and supplies, staff reshuffle and redeployment, inadequate supervision of health facilities, and nonpayment of community health worker incentives inhibited implementation of ICCM. Conclusion The study findings highlight key faciliators and barriers that should be considered by policy-makers, district health managers, ICCM supervisors, health facility managers, and co-operating partners, in designing context-specific strategies, to ensure successful implementation of ICCM in local health systems.